2016
DOI: 10.1016/j.immuni.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The TNF Receptor Superfamily in Co-stimulating and Co-inhibitory Responses

Abstract: Summary Cytokines related to Tumor Necrosis Factor (TNF) provide a communication network essential for coordinating multiple cell types into an effective host defense system against pathogens and malignant cells. The pathways controlled by the TNF superfamily differentiate both innate and adaptive immune cells as well as modulate stromal cells into microenvironments conducive to host defenses. Receptors in the TNFSF family activate diverse cellular functions, from production of type 1 interferons to the modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
310
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(331 citation statements)
references
References 225 publications
5
310
0
3
Order By: Relevance
“…Previous studies have demonstrated that B7-H3 participates in both immune stimulatory and inhibitory signals, 20 while TNFSF7 involves in stimulatory signals. 19 Therefore, our findings may provide significant prognostic factors and help to develop new target therapy.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Previous studies have demonstrated that B7-H3 participates in both immune stimulatory and inhibitory signals, 20 while TNFSF7 involves in stimulatory signals. 19 Therefore, our findings may provide significant prognostic factors and help to develop new target therapy.…”
Section: Discussionmentioning
confidence: 83%
“…18,19 However, the gene wide alterations of B7 and TNFR families remain largely unknown in colorectal cancer (CRC). Here, the frequency of B7 and TNFR gene alterations (including mutations, amplifications, and deletions) across 6 studies in colorectal cancer were shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T-cell expansion, effector differentiation, migration and survival are potentiated by signals from costimulatory receptors belonging to the TNFR superfamily whose expression are induced following initial antigen stimulation and CD28 costimulation [78][79][80]. The ligands for these receptors are typically expressed on PAMP-activated dendritic cells, and agonists to these costimulatory receptors thus provide critical signals for programming T-cell effector functionality that are otherwise lacking during steady-state antigen presentation [81].…”
Section: Immunotherapies Overcome Tumor-induced Immunosuppressionmentioning
confidence: 99%